SISTEM APLIKASI MONITORING REQUEST PENGADAAN BARANG BERBASIS MOBILE PADA HOTEL KENCANA PATI (Information Technology and Telematics, 2015)
Abstract Hotel kencana Pati is star hotel * * * in starch, precisely on jalan RA Kartini no.8, Pati. So far the monitoring systems and procurement of goods in this hotel still use manual system. Processing data that is done manually give rise to some of the problems as, delays in information so as to cause inaccurate data. Application system that can be on the monitoring of the procurement of goods and developed by a method of waterfall consisting of analysis(analysis) , design a system(design), programming(coding), testing a system(testing). Design system using UML, consisting of Use Case a diagram, Class Diagram, Activity Diagram, Sequence Diagram. The application made by using the language of PHP programing MySQL database and that can be accessed using mobile to facilitate the reservations in doing the kitchen goods meet the needs of customers in the hotel . This study has been produce an application that can be on the monitoring of kitchen goods part when goods discharged.Currently monitoring request the application of the procurement of goods hotel kencana starch use the domain of free with the address http://kencanapati.hol.es/kencanapati. But thus away will use the domain and hosting service that paid for security data in a hotel kencana Pati. Keywords: information systems, the library, texts books, mobile